Women’s Fluid Spaces and Gendered Spatial Orientations in Victorian Literature and Culture. - Arias-Doblas, María Rosario; Borham Puyal, Miriam; Monrós Gaspar, Laura; Pettersson, Lin Elinor (Ediciones Universidad de Cantábria, 2021)
In this roundtable we focused on the spatial significance of ‘orientation’, implying movement, and process, for Victorian women, engaging with the mobility turn, or “the mobility paradigm” in the study of women’s liminal spaces in the Victorian period. Drawing on Sara Ahmed’s Queer Phenomenology: Orientations, Objects, Others (2006), and other critics, we explored Victorian fluid spaces where the private and the public divide is negotiated, which, coupled with the break-up of temporal boundaries in some instances, underlines how embodied subjectivities benefit from being oriented towards other bodies and spaces. Finally, this roundtable considered the interaction of temporal and spatial dimensions in the analysis of women’s fluid positions in Victorian times, and in relation to the dynamic interstitial spaces inhabited by women in the nineteenth century. This led us to examine the meanings generated in re-positioning ourselves in relation to the past as regards women and mobility in the Victorian period.
https://www.editorialuc.es/node/17
Keywords: Mujeres - Reino Unido - S. XIX; Relaciones entre mujeres; Victorian women; Orientation; Female spaces; Liminality; Entertainment; Women's clubs; Spiritualism; London; New Woman